Influence of Advancing Biological Maturation on Aerobic and Anaerobic Power and on Sport Performance of Junior Rowers: A Longitudinal Study - Almeida-Neto, Paulo Francisco de; Silva, Luiz Felipe Da; Miarka, Bianca; De Medeiros, Jason Azevedo; de Medeiros, Rafaela Catherine da Silva Cunha; Teixeira, Rafael Pereira Azevedo; Aidar, Felipe J.; Cabral, Breno Guilherme De Araujo Tinoco; Dantas, Paulo Moreira Silva (Frontiers in Physiology, 2022)
Background: Researches are linking Biological Maturation (BM) with the performance of adolescent rowers from both genders. Despite this, there is still not enough information about the influence of BM advancement correlating to sports, aerobic and anaerobic performance in adolescent athletes at the sport modality rowing. Objective: Investigate the influence of Biological Maturation on sports performance and aerobic and anaerobic power in adolescent rowing athletes. Methods: A longitudinal observational study, developed over three years, with a sample of 52 adolescents, rowing athletes, of both genders (61% male and 39% female) mean age of 16.0±0.5 years old at the start and 18.4± 0.5 years old at the end of the study. Analysis was performed once a year. BM was evaluated through maturational groups generated from Age Peak Height Velocity; maximum aerobic power (VO2Max (ml/kg/min)) and mean anaerobic power (Watts) through the ergometer test (indoor rowing); peak anaerobic power (Watts) through a mathematical model derived from competition time, to determine sports performance analyzed the race time during world championship tryouts. Results: The advancement of BM influenced the reduction of the test time and increase of the mean anaerobic power (Watts) in indoor rowing (η2p> 0.36, p<0.05), as well as an improvement in performance in sports competition (η2p> 0.35, p< 0.05). However, the advancement of BM did not affect VO2Max (ml/kg/min) in young elite rowing athletes of both sexes (p>0.05). Conclusion: Advances in biological maturation have been shown to influence the anaerobic and sports performance (reduction of the execution time in 2,000-m) of adolescent rowing athletes of both genders.